The interaction of peptides and proteins with nanostructures surfaces: a challenge for nanoscience. (June 2019) - Brancolini, Giorgia; Bellucci, Luca; Maschio, Maria Celeste; Di Felice, Rosa; Corni, Stefano
Abstract: The impact of nanotechnologies in biomedicine and biotechnology is becoming more and more evident. It imposes practical challenges, for instance, raising specific issues on the biocompatibility of nanostructures. Nanoparticles are characterized by a high surface-to-volume ratio, which makes them reactive to foreign species. Thus, when proteins or peptides approach an inorganic nanoparticle, as well as a flat surface, they are likely to interact with the substrate to some extent. This interaction is crucial for applications in drug delivery, imaging, diagnostics, implants, and other medical devices. Specifically, gold nanoparticles are highly versatile and particularly appealing. It is widely accepted that the surfaces of nanoparticles adsorb proteins either transiently in the soft corona layer or permanently in the hard corona layer. As a consequence, the protein structure and/or function may undergo profound adjustments or remain conserved. Detailing the interaction of different inorganic substrates with proteins and peptides at the atomic level, and designing ways to control the interaction, is the key for biomedical applications of nanoparticles, both from a fundamental viewpoint and for practical implementations. In the last decade, we have addressed protein–nanoparticle interactions, focusing on interfaces of gold surfaces and nanoparticles with amyloidogenic peptides and protein models. We have developed classical force fields, performed advanced molecular dynamics simulations, and compared computational outcomes with data from nuclear magnetic resonance experiments. Protein–gold complexes with differently coated gold nanoparticles have been modeled to explore the effects of charge and size on the protein structure. Our work unravels that a complex interplay between surface properties and characteristics of the biological adsorbate determines whether peptide conformation is influenced and whether protein aggregation is accelerated or inhibited by the presence of the substrate. General guidelines to cope with amyloidogenic proteins could be inferred: these can be essentially summarized with the necessity of balancing the hydrophobic and electrostatic interactions that the amyloidogenic proteins establish with the coating moieties. Graphical abstract: Image 1